PERCEPTION OF SINGLE MALE AND SINGLE FEMALE TOWARDS MARRIAGE, SEX AND BEING SINGLE - Singh, Amandeep (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The inequalities people encounter on a daily basis are not typical. When the status of being single is cited as abnormal, stigmatization and inequality are also seen as abnormal behaviors. The way singles are viewed in relation to marriage reveals both their positive and negative sentiments. To find out what kind of perspectives single people have about marriage, their perceptions and attitudes toward marriage and marital status are examined. Different perspectives on marriage and married life are held by single people. Given this context, the current study attempted to compare and examine the opinions and attitudes of single men and women toward marriage, sex, and being single. To contrast and look into the reasons behind the continued single status of these men and women.